Computerized exercise program does not affect stress levels of asymptomatic VDT users. - Hinman M; Ezzo L; Hunt D; Mays A (Journal of Occupational Rehabilitation)
The purpose of this study was to determine whether a computerized exercise program could reduce stress levels in office workers who use video display terminals (VDTs). Fifty workers were randomly assigned to either an exercise or a control group. Twenty-four subjects were instructed to exercise twice a day for 15 minutes per session for a period of 8 weeks; the remaining 26 subjects in the control group were given no exercise program. Four dimensions of stress were measured before and after the exercise period using the Personal Strain Questionnaire (PSQ), a self-reported measure of physical and psychological stress. A multivariate T-test (Hotelling's T2) was used to compare changes in stress levels between the two groups of workers, but no significant differences were found. Further analysis of the exercise group revealed that difference in compliance rates among workers did not significantly influence changes in stress levels. These results indicate that this type of exercise program does not reduce stress in asymptomatic VDT users.